Longitudinal reciprocal relationship between media violence exposure and aggression among junior high school students in China: a cross-lagged analysis - Yifei Dou; Meng Zhang (Frontiers in Psychology)
IntroductionIncreasing evidence has shown that media violence exposure can influence individual aggression. However, the question of whether there is a causal relationship between media violence exposure and aggression remains complex and contentious. This study aims to examine the dynamic reciprocal relations between media violence exposure and aggression among junior high school students in China.MethodsUsing the Exposure to Violent Media Questionnaire (ETVMQ) and the Buss-Warren Aggression questionnaire (BWAQ), 259 junior high school students were tracked three times over a period of 1 year. A cross-lagged panel model was constructed to analyze the reciprocal relationship between media violence exposure and aggression over time.Results(1) Media violence exposure and aggression were significantly and positively correlated in all three assessments. (2) Cross-lagged analysis revealed that media violence exposure at Time 1(T1) significantly positively predicted aggression at Time 2(T2), and subsequently significantly positively predicted media violence exposure at Time 3(T3). Additionally, media violence exposure at T2 significantly positively predicted aggression at T3. (3) Multi-group analysis revealed that gender, family economic status, and family location had no significant moderating effects on the cross-lagged effects between media violence exposure and aggression. The cross-lagged effects did not differ by gender, family economic status, or family location.ConclusionThere is a positive reciprocal relationship between media violence exposure and aggression among Chinese junior high school students, and this reciprocal relationship demonstrates stability across gender and family environments. Media violence exposure is not only a risk factor for increasing aggression among Chinese junior high school students but also a negative outcome of high aggression.